OPOSIÇÃO NO SERTÃO: a construção da distinção entre música caipira e música sertaneja - ALLONSO, GUSTAVO (Outros Tempos: Pesquisa em Foco - História, 2013)
This article shows how the idea of purity and authenticity in rural genres was created in the academy in the 1950s and spread until today. Marxists, folklorists, and populism theorists united themselves in order to classify música sertaneja as a non-authentic musical genre.  On the other hand they suggested that música caipira was the authentic representation of the Brazilian peasant, who supposedly suffered from the expansion of the capitalism in the rural areas. This analyses often underestimate how Brazilian peasant felt about the modernization of the country.